Detection of Ascitic Feline Coronavirus RNA from Cats with Clinically Suspected Feline Infectious Peritonitis - SOMA, Takehisa; WADA, Makoto; TAHARAGUCHI, Satoshi; TAJIMA, Tomoko (Journal of Veterinary Medical Science, 2013)
Ascitic feline coronavirus (FCoV) RNA was examined in 854 cats with suspected feline infectious peritonitis (FIP) by RT-PCR. The positivity was significantly higher in purebreds (62.2%) than in crossbreds (34.8%) (P<0.0001). Among purebreds, the positivities in the Norwegian forest cat (92.3%) and Scottish fold (77.6%) were significantly higher than the average of purebreds (P=0.0274 and 0.0251, respectively). The positivity was significantly higher in males (51.5%) than in females (35.7%) (P<0.0001), whereas no gender difference has generally been noted in FCoV antibody prevalence, indicating that FIP more frequently develops in males among FCoV-infected cats. Genotyping was performed for 377 gene-positive specimens. Type I (83.3%) was far more predominantly detected than type II (10.6%) (P<0.0001), similar to previous serological and genetic surveys.